Understanding the privacy disclosure behavior and privacy concerns on short-form video platforms: an empirical investigation - Lu, Heng; Wei, Aiye; Li, Xin (Frontiers in Psychology, 2025)
In recent years, platform user privacy leaks have occurred frequently, heightening users’ privacy concerns, which may directly affect their behavior on short video platforms. Based on communication privacy management theory, this study constructs a conceptual model of factors influencing the privacy disclosure behavior of short video users from the perspectives of both peer privacy concerns and institutional privacy concerns. Data from 302 short video users were collected via an online questionnaire and analyzed using structural equation modeling. The results indicate that perceived peer risk and information sensitivity positively influence peer privacy concerns; the effectiveness of privacy protection technology and privacy policies negatively influence institutional privacy concerns; information sensitivity also positively affects institutional privacy concerns; both institutional and peer privacy concerns negatively affect users’ privacy disclosure behavior; and institutional privacy concerns positively influence peer privacy concerns. The study discusses how these findings extend the application of communication privacy management theory in the context of short video platforms, highlighting the intertwined nature of institutional and peer-induced privacy risks. Practical implications for platform designers and policymakers are offered to enhance user trust and promote responsible privacy management.